Optimizing fodder yield and quality through integrated organic nutrient amendments in multi-crop system - Onte, Santosh; Fiskey, Vrushabh Vijay; Melavanki, Manjunath S.; Angadi, Airadevi P.; Pyati, Prasanna S.; Singh, Magan; Kumar, Dileep; Kochewad, Sanjivkumar Angadarao; Kumar, Sudhir; Om, Hari; Meena, Vijendra Kumar; Garg, Kamal; et al. (Frontiers Media SA, 2025)
The increasing demand for organic fodder has highlighted the need for sustainable agricultural practices that optimize both yield and quality. However, research on integrated organic nutrient management in multi-crop systems remains limited, especially concerning its impact on forage productivity and nutritive value. This study aims to investigate the effects of integrated organic nutrient amendments on the yield and quality of multi-crop system. Conducted during the period 2018 to 2021 using a randomized complete block design, the experiment encompassed seven treatments, each replicated three times. These treatments comprised of different combination of farmyard manure (FYM), Plant growth promoting rhizobacteria (PGPR) and foliar spray of panchagavya for maize (M), berseem (B), and cowpea (C) and a treatment with recommended dose of fertilizers. The treatment includes T1: 100% RDN through FYM (M) - No application (B) - No application (C); T2: 50% RDN through FYM + PGPR + 3% foliar spray of panchagavya (M) – PGPR + 3% foliar spray of panchagavya (B) – PGPR + 3% foliar spray of panchagavya (C); T3: 75% RDN through FYM + PGPR (M) - PGPR (B)- PGPR (C); T4: 100% RDN through FYM + PGPR (M) - PGPR (B) - PGPR (C); T5: 75% RDN through FYM + PGPR + 3% foliar spray of panchagavya (M) – PGPR + 3% foliar spray of panchagavya (B) – PGPR + 3% foliar spray of panchagavya (C); T6: 100% RDN through FYM + PGPR + 3% foliar spray of panchagavya (M) – PGPR + 3% foliar spray of panchagavya (B) – PGPR + 3% foliar spray of panchagavya (C), and T7: 100% RDF (M)- 100% RDF (B)- 100% RDF (C). Research findings revealed that the T6 treatment, involving T6: 100% RDN through FYM + PGPR + 3% foliar spray of panchagavya (M) – PGPR + 3% foliar spray of panchagavya (B) – PGPR + 3% foliar spray of panchagavya (C), yielded significant improvements in both green fodder of maize (35.4, 37.0, and 38.6 t ha-1), berseem (58.2, 60.0, and 60.6 t ha-1) and cowpea (25.7, 27.5, and 28.3 t ha-1) during 2018-19, 2019-20 and 2020-21, respectively. Furthermore, T6 significantly enhanced forage quality, as evidenced by higher crude protein (6.4–14.8%), ether extract (19.2–40.1%), and total ash (6.5–22.1%) contents, coupled with reductions in fiber components. These findings highlight the effectiveness of integrated organic nutrient amendments in enhancing both yield and quality, offering a sustainable strategy to improve livestock feed and promote environmentally friendly agricultural practices.